1996
DOI: 10.1089/cmb.1996.3.213
|View full text |Cite
|
Sign up to set email alerts
|

Delaunay Tessellation of Proteins: Four Body Nearest-Neighbor Propensities of Amino Acid Residues

Abstract: Delaunay tessellation is applied for the first time in the analysis of protein structure. By representing amino acid residues in protein chains by C alpha atoms, the protein is described as a set of points in three-dimensional space. Delaunay tessellation of a protein structure generates an aggregate of space-filling irregular tetrahedra, or Delaunay simplices. The vertices of each simplex define objectively four nearest neighbor C alpha atoms, i.e., four nearest-neighbor residues. A simplex classification sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
136
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(136 citation statements)
references
References 29 publications
0
136
0
Order By: Relevance
“…It is also applied to binding site identification (Peters et al, 1996), molecular mesh generation (Akkiraju & Edelsbrunner, 1996), and electrostatics calculations based on boundary elements (Liang & Subramaniam, 1997). Other computational geometry methods applied to biological questions include unweighted Delaunay tetrahedra for analysis of protein structures (Singh et al, 1996) and for recognition of protein folds in sequence threading (Munson & Singh, 1997). A recent advance in characterization of protein pockets is the discrete flow method used in conjunction with alphashape theory ; it has been applied to estimation of hydration changes due to osmotic stress of antithrombin , identification of potential binding sites for calcium ions in the Gla domain of prothrombin , and identification of the D-site binding pocket thought to contain the proton acceptor of tyrosine radical in photosystem I1 (Kim et al, 1997).…”
Section: Pocket and Cavity Analysismentioning
confidence: 99%
“…It is also applied to binding site identification (Peters et al, 1996), molecular mesh generation (Akkiraju & Edelsbrunner, 1996), and electrostatics calculations based on boundary elements (Liang & Subramaniam, 1997). Other computational geometry methods applied to biological questions include unweighted Delaunay tetrahedra for analysis of protein structures (Singh et al, 1996) and for recognition of protein folds in sequence threading (Munson & Singh, 1997). A recent advance in characterization of protein pockets is the discrete flow method used in conjunction with alphashape theory ; it has been applied to estimation of hydration changes due to osmotic stress of antithrombin , identification of potential binding sites for calcium ions in the Gla domain of prothrombin , and identification of the D-site binding pocket thought to contain the proton acceptor of tyrosine radical in photosystem I1 (Kim et al, 1997).…”
Section: Pocket and Cavity Analysismentioning
confidence: 99%
“…Using a geometric accounting based on the Delaunay tessellation for three-and four-body interactions, Singh et al (1996) suggested that four-body interactions may indeed be important. Such multi-body contributions to protein potentials are reasonable from a geometric point of view, if we approximate each residue as a sphere centered on its C" location.…”
Section: P J Munson and R K Singhmentioning
confidence: 99%
“…For the first time, we have used Delaunay triangulation for tessellation of protein surface atoms to measure surface complementarity. Delaunay's triangulation has been previously used on proteins in a different application for creation of simplices to evaluate four-body nearest neighbor propensities of amino acids [25]. A related tessellation technique, Voronoi polyhedra and alpha-complex have been used to measure atom packing, but the implementation is different.…”
Section: Discussionmentioning
confidence: 99%